2016
DOI: 10.1166/jnn.2016.10832
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior of a Novel Organic–Inorganic Hybrid: Micro/Nano-Tin Fluorophosphate Glass-Polycarbonate

Abstract: The rheological behavior of a novel, binary organic-inorganic hybrid consisting of an ultra-low Tg tin fluorophosphate glass (Pglass) and polycarbonate (PC) was investigated using oscillatory rheometry. It was found that the complex viscosity of the hybrid showed Pglass content dependence. Under low Pglass content (10-30%), the complex viscosity of the hybrid was lower than that of pure PC. While the complex viscosity was dramatically increased and higher than that of pure PC with the content of Pglass above 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…They combine the favorable optical properties of fluoride glasses with the higher mechanical and thermal stability of phosphate glasses. Aluminum-containing fluoride phosphate glasses have attracted considerable attention as matrices for rare-earth dopants for active lasers, amplifier glasses, and for photoluminescence in the visible region. In addition, nanoparticle-containing systems, inorganic–organic hybrid systems, and biomaterials are being studied . The goal of tailoring the particular properties of these attractive glasses requires a comprehensive understanding of their structural organization.…”
Section: Introductionmentioning
confidence: 99%
“…They combine the favorable optical properties of fluoride glasses with the higher mechanical and thermal stability of phosphate glasses. Aluminum-containing fluoride phosphate glasses have attracted considerable attention as matrices for rare-earth dopants for active lasers, amplifier glasses, and for photoluminescence in the visible region. In addition, nanoparticle-containing systems, inorganic–organic hybrid systems, and biomaterials are being studied . The goal of tailoring the particular properties of these attractive glasses requires a comprehensive understanding of their structural organization.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers [13,15] have demonstrated that the TFP-glass can enhance the flowability of polar polymer. As can be seen from Fig.…”
Section: Rheological Behavior and Storage Modulus Of Pet/tfp-glass Comentioning
confidence: 99%
“…And the reason will be discussed in "The enhancement mechanism of flowability". Furthermore, with the increase of TFP-glass, the composite exhibits more obvious shear-thinning behavior, which may attribute to the nonlinear chemical and physical interactions between the hybrid components [13,15].…”
Section: Rheological Behavior and Storage Modulus Of Pet/tfp-glass Comentioning
confidence: 99%
See 2 more Smart Citations